Método de avaliação de algoritmos de detecção e remoção de sombra em imagens aéreas - Doth, Ricardo Vinicius (2018)
Wide Area Motion Imagery (WAMI) systems acquire large area aerial images in real time to provide accurate situational awareness information from a region (BLASCH et al., 2014). This system is applied for urban aerial monitoring. Unfavorable environmental conditions, such as shadow regions, are factors that increase system complexity by compromising the effectiveness of tracking algorithms and human visual interpretation (PORTER; FRASER; HUSH, 2010). Several techniques of shadow removal in aerial images have been developed, however due to the characteristics of the shadow and aerial image, a specific method to evaluate and compare the removal is unknown. The main objective of this study is to develop a method to evaluate shadow removal algorithms in aerial images acquired by the WAMI system. This work proposes a radiometric approach modifying the illumination in a controlled environment, simulating an aerial scene, acquiring images with and without the presence of shadows. The image with shadows is processed by the evaluated shadow removal algorithm, with the ideal output being the shadow free image. Shadow detection is evaluated using the confusion matrix concept. Shadow removal is evaluated using the structural similarity index (SSIM). As a result the reduced scale aerial scene model is presented to generate shadow and freeshadow images and the evaluation of 3 shadow removal methods using the data sets of images obtained from the scale model applying the methodology developed.